2018
DOI: 10.1002/2017wr021692
|View full text |Cite
|
Sign up to set email alerts
|

Soil Texture Often Exerts a Stronger Influence Than Precipitation on Mesoscale Soil Moisture Patterns

Abstract: Soil moisture patterns are commonly thought to be dominated by land surface characteristics, such as soil texture, at small scales and by atmospheric processes, such as precipitation, at larger scales. However, a growing body of evidence challenges this conceptual model. We investigated the structural similarity and spatial correlations between mesoscale (∼1–100 km) soil moisture patterns and land surface and atmospheric factors along a 150 km transect using 4 km multisensor precipitation data and a cosmic‐ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 50 publications
6
82
3
Order By: Relevance
“…Many researchers have reported that soil moisture is commonly thought to be controlled by land surface characteristics, such as topography, vegetation, and deduced root structure, and landform at small scales, and by atmospheric factors, such as precipitation and evaporation patterns, at larger scales (Seyfried, 1998; Entin et al, 2000; Brocca et al, 2010; Cho and Choi 2014). Using empirical orthogonal functions (Champa and Mohanty, 2010; Wang et al, 2017a) and cosmic‐ray neutron rover methods (Dong and Ochsner, 2018), some evidence suggests that soil texture is a large‐scale factor for soil moisture variation. In the current study, we applied the MEMD method first across a regional scale and investigated the relative roles of meteorological forcings and local factors in controlling soil moisture patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported that soil moisture is commonly thought to be controlled by land surface characteristics, such as topography, vegetation, and deduced root structure, and landform at small scales, and by atmospheric factors, such as precipitation and evaporation patterns, at larger scales (Seyfried, 1998; Entin et al, 2000; Brocca et al, 2010; Cho and Choi 2014). Using empirical orthogonal functions (Champa and Mohanty, 2010; Wang et al, 2017a) and cosmic‐ray neutron rover methods (Dong and Ochsner, 2018), some evidence suggests that soil texture is a large‐scale factor for soil moisture variation. In the current study, we applied the MEMD method first across a regional scale and investigated the relative roles of meteorological forcings and local factors in controlling soil moisture patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, high‐spatial‐resolution soil moisture observations as provided by remote sensing products are valuable information to integrate in the models even if only the surface soil is detected (Barrett et al, ; Paloscia et al, ). The use of roving cosmic ray neutron sensing could be another promising tool for inferring soil moisture status and their integration into hydrological models, also because the signal integrates over most of the root zone (Chrisman & Zreda, ; Dong & Ochsner, ; Schrön et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel study, we discovered a strong negative correlation between mesoscale patterns in sand content and soil moisture (Dong & Ochsner, ); therefore, sand content (%) is used in the regression kriging approach as a proxy for the various soil properties that control soil water retention. For every Mesonet site and each grid point, sand content at 5, 25, and 60 cm was estimated using the 10‐m resolution Gridded Soil Survey Geographic (gSSURGO) Database (Soil Survey Staff, ).…”
Section: Methodsmentioning
confidence: 99%